2010
DOI: 10.1161/circgenetics.109.907642
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Genomic Variation in the LPA Locus and Its Relationship to Plasma Lipoprotein(a) in South Asians, Chinese, and European Caucasians

Abstract: Background— Functional copy number variation in the apolipoprotein(a) gene ( LPA ) underlies a variable number of protein kringle domains repeated in tandem in the lipoprotein(a) [Lp(a)] particle. Genomic analysis of LPA , including both single-nucleotide polymorphisms (SNPs) and kringle IV type 2 (KIV-2) copy number, has yet to be performed. Methods and Results— Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
95
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(110 citation statements)
references
References 43 publications
12
95
3
Order By: Relevance
“…Serum Lp(a) concentrations are reported to be genetically determined ( 2 ) and different in various races ( 33 ). Although related large population studies have been performed in individuals of European or American origin, it is worth exploring this subject in Asians.…”
Section: Discussionmentioning
confidence: 99%
“…Serum Lp(a) concentrations are reported to be genetically determined ( 2 ) and different in various races ( 33 ). Although related large population studies have been performed in individuals of European or American origin, it is worth exploring this subject in Asians.…”
Section: Discussionmentioning
confidence: 99%
“…The question arises, to what extent does this pattern vary across ethnicity? Studies in South Asians, Chinese, and Caucasians revealed that SNP rs10455872 was prevalent only in the latter (29). In addition, SNP rs6415084 within the same haplotype block as the KIV repeat polymorphism was associated with both Lp(a) concentrations and the size polymorphism in all three ethnic groups.…”
Section: Downloaded Frommentioning
confidence: 92%
“…Ronald et al (32) identified a set of nine SNPs accounting for 30% of the variation in Lp(a) con centration, five of which overlapped with a set of seven SNPs identified by others (31). Six of these nine SNPs, of which four had previously been reported (29,30), pre dicted Lp(a) concentrations conditional on the number of KIV repeats. Accounting for apo(a) size, SNPs rs3798220 and rs10455872 were associated with Lp(a) concentra tions, and together explained 22% of Lp(a) variance.…”
Section: Downloaded Frommentioning
confidence: 98%
See 2 more Smart Citations